EDUCATIONAL INFORMATION PORTALS AS AN ADDITIONAL RESOURCE FOR TEACHING COMPUTER SCIENCE IN SECONDARY SCHOOLS - A. Karymsakova; Zh. Akhaeva; A. Kassymova (Bulletin of Toraighyrov University. Physics & Mathematics series, 2021)
This article contains information about the use of educational portals in teaching the subject «Computer Science» in a secondary school. The current situation with the pandemic, the rapid transition of educational organizations to distance learning, the lack of full-fledged teacher-student interaction, and at the same time the lack of proper assimilation of information requires school teachers to modernize teaching approaches with an emphasis on the independent work of students. At the moment, Kazakhstan’s education is undergoing a number of reforms, in particular digitalization and automation of the educational process, the introduction of e-learning in schools in Kazakhstan. The rapid development of information technologies is replacing traditional static websites used for online education with interactive intellectual portals that provide additional opportunities for learning new, more in-depth knowledge that cannot be achieved using only traditional teaching methods. The article contains a comparative analysis of educational portals proposed by the Ministry of Education and Science of the Republic of Kazakhstan for additional distance self-education of schoolchildren. The analysis was carried out according to the following criteria: the availability of materials of the school course «Computer Science», the method of submitting new material, compliance with the requirements of the state standard, a way to consolidate new knowledge in the form of tests, simulators, practical tasks, and more. It was found out that not all the proposed portals contain materials on a school subject, many portals require registration and a fee for use, some portals are only in the state language, which limits universal access.